Answer:
[tex]64a^3b^3-125c^3=(4ab-5c)(16a^2b^2+40abc+25c^2)[/tex]
Step-by-step explanation:
You have the following polynomial:
[tex]64a^3b^3-125c^3[/tex]
This expression is of the form:
[tex]x^3-y^3[/tex]
that is, a difference between cubes. The factorization of such a polynomial is given by:
[tex]x^3-y^3=(x-y)(x^2+2xy+y^2)[/tex]
You apply the last expression to the polynomial given in the problem. But first you have:
[tex]x^3=64a^3b^3\\\\y^3=125c^3\\\\x=4ab\\\\y=5c[/tex]
finally, you obtain:
[tex]64a^3b^3-125c^3=(4ab-5c)((4ab)^2+2(4ab)(5c)+(5c)^2)\\\\64a^3b^3-125c^3=(4ab-5c)(16a^2b^2+40abc+25c^2)[/tex]